PATHOGENETIC MECHANISMS OF AFTER STRESS PSYCHOLOGICAL MALADJUSTMENT OF POLICEMAN’S AFTER PARTICIPATION IN THE ANTI-TERRORIST OPERATION - Kozira, Piotr (PSYCHOLOGICAL JOURNAL, 2016)
Employees of the Interior Ministry of Ukraine in conditions of permanent the Political, economic and social changes of the fighting are directly involved in them and suffer the consequences of all these events in the form of poststress psychological maladjustment. The degree of personality maladjustment due to the effects of stress and the level of distress depends on many factors, including the characteristics and traits. Especially important is the understanding of the interaction and the role of these factors in the formation of pathogenic mechanisms poststress maladjustment for its subsequent correction, forecasting and prevention. Purpose of the study. The aim of this study is to develop a model of pathogenetic mechanisms of development of poststress of psychological maladjustment XYZ employees of MIA of Ukraine after participating in the ATO. Materials and methods. It was conducted clinical and psychological examination of psychodiagnostic and psychological state of the 205 employees of MIA of Ukraine. Of these, 148 participated in the conduct of the ATO. The results were processed using principal components factor analysis method. Criterion sampling adequacy Kaiser-Meyer-Olkina for the sample was 0.62. The criterion of sphericity showed Barletta significance level <0.01. Results of the study. Establishing an emotional-affective and psychopathic options poststress psychological maladjustment among employees of MIA of Ukraine, took part in the ATO, which differ in the level and quality of disadaptation manifestations. Poststress psychological maladjustment consists of two entities with different origins and playing different roles in the formation of maladjustment. This structure of the new behavioral strategies and proper post-traumatic disorders. Each fixed structure, respectively variant maladjustment characterized by corresponding changes in the behavioral, emotional and cognitive areas of personality. The origins of maladjustment installed options are especially education and life experience. Prospects for further research is to develop on the basis of the proposed model of pathogenetic mechanisms, differentiated system psychocorrection different options poststress psychological maladjustment participants ATO.